2008 Computers in Cardiology 2008
DOI: 10.1109/cic.2008.4749078
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet transform coherence estimates in cardiovascular analysis: Error analysis and feasibility study

Abstract: Wavelet transform coherence (WTC) can provide insight into the transient linear order of the regulatory mechanisms, via the computation of time-frequency maps of the time-variant coherence. This paper presents a framework for applying WTC for quantitative analysis of coherence in cardiovascular variability research.Computer simulations were performed to estimate the accuracy of the WTC estimates and a method for determining the coherence threshold for specific frequency band was developed and evaluated. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Previous research with a similar application of WTC methods has shown comparable results with acceptable differences from the current study [19,20,23]. The differences in the values of the statistical measures and behavior with different values of the Morlet coefficient, ω 0 , were as expected based on the different types of signals under investigation.…”
Section: Discussionsupporting
confidence: 84%
“…Previous research with a similar application of WTC methods has shown comparable results with acceptable differences from the current study [19,20,23]. The differences in the values of the statistical measures and behavior with different values of the Morlet coefficient, ω 0 , were as expected based on the different types of signals under investigation.…”
Section: Discussionsupporting
confidence: 84%
“…4 we represent the wavelet coherence among the subjects S 1 , S 2 , and S 3 , using the definition in Eq. (12). From this figure, it becomes evident that there is a high degree of entrainment among all the subjects, for activity A1 and A6 with a period of about 12 seconds, and for activity A7 with a period of about 4 seconds.…”
Section: Group Entrainmentmentioning
confidence: 88%
“…C (k,s) x1,...,xN is calculated according to Eq. (12). Given this definition, we can also calculate a new measure, namely the entrainment level, between each 2 The figures in this section are best viewed in color.…”
Section: A Entrainment Networkmentioning
confidence: 98%
See 1 more Smart Citation
“…Although several authors have used wavelet techniques in the study of cardiovascular regulation (e.g., Brychta et al, 2006; Stankovski et al, 2013; Singh et al, 2018), only few papers are known to us which applied cross wavelet techniques for the analysis of blood-pressure and heart-rate variability (Keissar et al, 2006, 2008, 2010; Kashihara et al, 2009). The first papers of Keissar et al (2006, 2008) show principally the usefulness of this technique in the study of the ANS. In their 2010 paper these authors present the fluctuations of computed BRS values for supine subjects and during active standing up.…”
Section: Discussionmentioning
confidence: 99%